2019
DOI: 10.1108/md-10-2017-0947
|View full text |Cite
|
Sign up to set email alerts
|

Reaching organizational ambidexterity in the merger process: a temporal switching

Abstract: Purpose The purpose of this paper is to explore how a company reaches organizational ambidexterity during a merger process. Organizational ambidexterity refers to the proactive adaptations of an organization to simultaneously explore and exploit. Design/methodology/approach The paper presents a longitudinal case study of a public-private merger of two listed French companies. The data were collected from participant observation, interviews and archival documentation over two years. Findings The balance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…However, recent studies have indicated that integration is essentially a multi-stage dynamic process (Graebner et al. , 2017; Thelisson et al. , 2019; Quah and Young, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have indicated that integration is essentially a multi-stage dynamic process (Graebner et al. , 2017; Thelisson et al. , 2019; Quah and Young, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Static insights on the PMI have been very common. However, recent studies have indicated that integration is essentially a multi-stage dynamic process (Graebner et al, 2017;Thelisson et al, 2019;Quah and Young, 2005). In a seminal work that emphasizes the process aspect of integration, Haspeslagh and Jemison (1991) have identified four integration approaches: holding, preservation, absorption and symbiosis.…”
Section: Literature Review 21 Dynamic Post-merger Integrationmentioning
confidence: 99%
“…Symbiosis is advised when both acquirer–acquired interdependence and the acquired organization's autonomy are high. However, in practice, keeping the balance between control and autonomy or freedom is precarious or paradoxical task (Thelission et al. , 2019; Tabesh and Vera, 2020).…”
Section: Literature Review: the Role Of Culture In Pmimentioning
confidence: 99%
“…Azambuja and Islam, 2019;Bartels et al, 2006;Dackert et al, 2003;Edwards et al, 2017;Giessner, 2011; Pina e Cunha et al, 2019;Stahl et al, 2011;Stahl and Voigt, 2008;van den Steen, 2010;van Marrewijk, 2016;Veiga et al, 2000), and the more or less successful strategies of coping with the differences (e.g. Edwards and Edwards, 2015;Larsson and Lubatkin, 2001;van Dick et al, 2006;Thelisson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation